Investigating the environmental impacts and engineering performance of road asphalt pavement mixtures made up of jet grouting waste and reclaimed asphalt pavement - Oreto, Cristina; Veropalumbo, Rosa; Viscione, Nunzio; Biancardo, Salvatore Antonio; Russo, Francesca (Environmental research, 2021)
As a response to the reduction of environmental pollution and energy consumption in the maintenance or building of a road pavement, this research aims to provide innovative asphalt mixture solutions when designing asphalt base layers containing solidified Jet Grouting Waste (JGW) particles. This involved adding (or not) solutions made up from Reclaimed Asphalt Pavement (RAP) obtained by milling old pavements. The first step focused on a JGW and RAP leaching test before going on to design two non-traditional mixtures: a) a hot asphalt mixture made by replacing 4% of the limestone filler by the total weight of the aggregates with JGW (HMAJ), mixing all of them at a high temperature (160 ÷ 180°C), and b) a cold asphalt mixture made by adding 3% JGW as a filler, 70% RAP (CMRAJ), and 27% limestone by the total weight of the aggregates at low temperatures (40 ÷ 50°C). These innovative mixtures were investigated from the point of view of engineering performance by ascertaining their physico-mechanical features and environmental impact through a Life Cycle Assessment (LCA) test. Further comparison with traditional ones was then carried out using a hot mix asphalt (HMA) and a cold mixture made up from RAP, substituting a portion of the limestone aggregates (CMRA). Such mixtures are subject to special tender specification requirements. Engineering performance assessment showed that, compared with HMA, when JGW is added to both hot and cold mixtures, the ITS is 11% higher for HMAJ and CMRAJ, and cumulative strain is reduced by 17% for HMAJ and 39% for CMRA, while the cold asphalt mixtures (CMRA and CMRAJ) showed greater stiffness levels (on average 50%) at all test temperatures (10, 25, and 40°C). LCA analysis provided significant results for the solutions being compared. Specifically, use of HMAJ as the base layer helped save 65 g/m3 of CO2 compared with HMA, at the same time helping to reduce 29.7 kg of CO2eq./m3 global warming potential. On the other hand, the use of CMRA as the base layer, again compared with the HMA, helped save 45 g/m3 of phosphorous compound emissions in water. In terms of terrestrial ecotoxicity and human non-carcinogenic toxicity, the best performance was obtained using a CMRAJ mixture, whose indicators showed a 60% reduction compared with the HMA solution base layer. •Road asphalt mixtures using jet grouting waste and reclaimed asphalt pavement.•Waste chemical composition and leaching test analysis.•Designing base layers with hot and cold component-mixing procedures.•Assessing the life cycle of the designed road asphalt pavement stratigraphies.•Indirect tensile strength, water sensitivity, dynamic stiffness, and creep rate.